Book Reviews (Journal of Finance, 1989)
Book reviewed in this article: Stock Market Anomalies . By ELROY DIMSON, editor. Cambridge, UK: Cambridge University Press, 1988. Pp. xiii + 295. Bond Markets, Analysis and Strategies . By FRANK J. FABOZZI and T. DESSA FABOZZI. Englewood Cliffs, NJ: Prentice Hall, 1989. Pp. xx + 347. The Japanese Stock Market: Pricing Systems and Accounting Information . By SHIGEKI SAKAKIBARA, HIDETOSHI YAMAJI, HISAKATSU SAKURAI, KENGO SHIROSHITA, and SHIMON FUKUDA. New York: Praeger Publishers, 1988. Pp. xvi + 156.